2019
DOI: 10.1002/jlb.1a0918-349rr
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of iNOS expression in myeloid progenitor cells expedites neutrophil differentiation

Abstract: Neutrophils play important role in immunity and inflammation through diverse mechanisms. Reports from this lab and others have demonstrated involvement of NO in neutrophil adhesion, chemotaxis, bacterial killing, reactive oxygen species generation, neutrophil extracellular traps’ formation, and apoptosis. Constitutive expression of iNOS in human neutrophils has also been documented. The role of NO‐iNOS in neutrophil differentiation however remains ill‐defined. The present study was undertaken to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…In a recent study, we have demonstrated that the expression of both iNOS transcript and protein is significantly less in PMNs from newly diagnosed CML patients, 17 whereas its overexpression expedites neutrophilic differentiation of CML cells 27 . To further identify its significance in BCR–ABL leukemogenesis, we examined the effect of imatinib, a BCR–ABL kinase inhibitor on NO generation and iNOS expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we have demonstrated that the expression of both iNOS transcript and protein is significantly less in PMNs from newly diagnosed CML patients, 17 whereas its overexpression expedites neutrophilic differentiation of CML cells 27 . To further identify its significance in BCR–ABL leukemogenesis, we examined the effect of imatinib, a BCR–ABL kinase inhibitor on NO generation and iNOS expression.…”
Section: Resultsmentioning
confidence: 99%
“…3A–3D). Since, PMNs from imatinib responders are more mature than those from drug naive and imatinib nonresponders, and it has been shown that the expression of iNOS was augmented with maturity of neutrophils, 27 we next assessed iNOS expression in neutrophils progenitors and mature cells obtained from drug naive and imatinib nonresponders CML patients. Reduced nitrite level and iNOS expression were evident in the progenitors and mature differentiated PMNs of drug naive and imatinib‐resistant CML patients and no significant differences were noted among the cells exhibiting various stage of neutrophils differentiation (Supplemental Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were sacrificed to retrieve the tissues (liver, epididymal white adipose tissues, and hind limb skeletal muscle). Total nitrite (nitrate and nitrite) was estimated in serum (100 μL) and tissues (liver, eWAT, and skeletal muscle, 50 mg) using Griess reagent by reducing nitrate to nitrite using pre-activated cadmium pellets followed by deproteinization in tissue homogenates with 3% trichloroacetic acid [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative densitometry was performed using Image J software for Windows 64bit (NIH, Bethesda, MA, USA). Real time PCR was performed as described previously [ 46 ] with primers listed in Table S2 and normalized with 18S rRNA.…”
Section: Methodsmentioning
confidence: 99%